NEW SYNONYMY FOR TENTHREDO HYMALAYENSIS (RADOSZKOWSKY) (HYMENOPTERA : TENTHREDINIDAE) - SATNI, MALKLAT S.; SINGIH, DEVINDER (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1988)
Tenthredo incognita (Binghan), 1898) and T. incognita balatea (Rohwer. 1921) are supressed in synonymy to T hymalasensis (Radoszkowsky, 1872). Female and male external genitalia of this species has been illustrated for the first time.